KEMAMPUAN MEMAHAMI KATA 会 (huì), 能 (néng), dan 可以 (kěyǐ) DALAM KALIMAT BAHASA MANDARIN SISWA KELAS VIII SMP FRATER MAKASSAR - Dian Pratiwi; Misnawaty Usman; Nasharuddin Noni (Wen Chuang:Journal of Foreign Language Studies, Linguistics, Education, Literatures, Cultures, and Sinology, 2022)
DIAN PRATIWI, 2021. "Ability to Understand the Words (huì), (néng), and (kěyǐ) in Chinese Sentences for Class VIII Students of Frater Makassar Junior High School". Thesis. Mandarin Education Study Program, Department of Foreign Languages, Faculty of Languagesand Letters. Makassar State University (supervised by Misnawaty Usman and Nur Nasharuddin Noni).This research was conducted to obtain data and information about the ability to understand the words (huì), (néng), and (kěyǐ) of Class VIII Junior High School Frater Makassar. This type of research uses descriptive quantitative. The population of this research is the eighth grade students of SMP Frater Makassar which consists of 8 classes with 248 students. Sampling using random sampling technique with a sample of class 8A consisting of 33 students. The research data was obtained through a test of the ability to understand the words (huì), (néng), and (kěyǐ) in Chinese sentences. Data analysis using the average search and percentage techniques with the results of 70.45% included in the category of being quite able to understand. Thus, this study shows that the ability to understand the words (huì), (néng), and (kěyǐ) in Chinese sentences of Class VIII students of SMP Frater Makassar is quite capable of understanding (70.45%). Keywords: Understanding Ability, (huì), (néng), and (kěyǐ), Mandarin Language